High density EEG: Could it be useful for language localization?. Issue 3 (March 2016) - Genetti, M.
Abstract : In patients with pharmacoresistant epilepsy, pre-surgical planning requires precise localization of both the epileptic zone and the eloquent cortical areas. In some patients, electrode implantation is necessary to achieve this goal. Electrocortical stimulation (ECS) of the individual contacts has been established as the gold-standard for individual cortical localization of critical brain regions. However, ECS is not suitable for all patients. Therefore, to overcome the limitations of ECS, non-invasive and invasive functional mapping approaches based mainly on functional magnetic resonance imaging (fMRI) and subdural electrocorticographic recordings (ECoG) have been developed. Although fMRI is frequently used as a complementary tool for surgical planning, less is known about the use of high density electroencephalography (EEG). Very few high density EEG studies have shown consistent results for language lateralization. Here, we will discuss our experience with 256-channel EEG in language localization in the individual brain.